(untitled) (Journal of the Entomological Research Society, 2021)
Holcocephala calva (Loew, 1872) forages primarily from dead twig tips, capturing and immobilizing prey in flight or in a hover near the foraging/feeding site. Identified prey is in eight orders [Araneae, Blattodea (Isoptera), Coleoptera, Diptera, Hemiptera, Hymenoptera, Lepidoptera, and Psocoptera], with Hymenoptera (42.3%) and Diptera (33.1%) making up 75.4%. Mating occurs in the tail-to-tail position. Females oviposited by dropping one egg at a time onto the ground. Holcocepala calva exhibit a daily rhythm of activity with peak periods between 6:00–10:00 AM of foraging, male searching flights for females with which to mate, mating, and ovipositing. Throughout the day the most common grooming consists of the hind tarsi and tibiae being rubbed together and one or both hind tarsi and tibiae are used to stroke the sides of the abdomen. Habitat, flight patterns, daytime and nighttime resting behavior, light levels and vision, and predators and parasites also are discussed.